The crystal structure of N-cyclopentyl-3-hydroxy-4-methoxybenzamide, C13H17NO3 - Zhang Jingxiao; Guo Shubin; Guo Yongnan; Yang Yanliang (Zeitschrift für Kristallographie - New Crystal Structures)
C13H17NO3, monoclinic, Cc (no. 9), a = 11.6502(8) Å, b = 13.8752(8) Å, c = 7.9644(5) Å, β = 106.051(2)°, V = 1237.25(14) Å3, Z = 4, R gt(F) = 0.0427, wR ref(F 2) = 0.1023, T = 170 K.